UPAYA KEBERLANJUTAN DESAIN PADA RAK PAJANG MENGGUNAKAN METODE ATUMICS - Wismoyo, Erlana Adli; Hadiansyah, Mahendra Nur; Muarrafah, Annisa; Kurnia, Dewanti Anggun; Nursetyo, Raudinahaq Syarafina; Nursa’adah, Silvy Amelia (Program Studi Desain Interior Unikom, 2023)
The goal of the research is to provide an explanation of how retail shelves are designed with sustainability in mind, utilizing the Atumics model. Design sustainability is one endeavor to connect the elements of space with human activity in order to remain sustainable. It addresses the conditions and bad repercussions in an environmental crisis, health, and user comfort. Using the model atumics, this research attempts to address the issue of one of the space elements, specifically furniture in the shape of a shed shelf that is used to keep the store's necessities and to exhibit the product for sale. The Atumics model is a sustainable furniture design that combines elements of tradition and current design by combining many design references with pre-existing vintage goods. In order to process data from observations and literary studies, this research use qualitative methodologies. It is anticipated that the findings of this study will serve as the foundation for the development of new furniture innovations with broader designs that can be sold to a larger market. smaller in size and form, and simple to modify to fit the demands of the current market. Furniture is not only utilized in retail establishments; it can also be positioned in other establishments until the property is used as a storage facility